2050 LCOE improvement using new molten salts for thermal energy storage in CSP plants. (May 2016) - Parrado, C.; Marzo, A.; Fuentealba, E.; Fernández, A.G.
Abstract: The solar conditions in northern Chile, in particular the Atacama Desert, which presents an annual global radiation value of 2500 kW h/m 2 and an index of direct normal irradiance (DNI) of 3500 kW h/m 2, are among the best worldwide for capturing and storing solar energy. These features are of major importance when considering the saline deposits that are concentrated in this area. There are several factors that make CSP technology an ideal resource for a successful development in northern Chile, highlighting the excellent solar resource and their combination with storage could supply energy to mining industry, which requires energy 24 h per day. The focus of this paper is to develop an economic analysis for computing a projection of LCOE between 2014 and 2050 from a 50 MW CSP plant with five different composition of salts for it TES. Two different scenarios are considered for this study: IEA BLUE Map Scenario and Roadmap Scenario. Additionally, a comparison between the LCOE in the north of Chile and the most influential countries in solar energy (Spain and USA) is made. The research basis lay on contribution of recent Chilean plans together with international researches in order to support the great potential of the implementation of CSP plant in the north of Chile. The results show that new proposed molten salts reduce considerably the storage cost. Thus, it can contribute to a promising future of the growth of CSP in the Plataforma Solar del Desierto de Atacama (PSDA) at north of Chile.